The Use of Unified Acceptance Technology Model for Travel Mobile Applications - Bakar, Nurzehan Abu; Hashim, Nik Alif Amri Nik; Othman, Nur Azimah; Muhammad, Nur Hafizah; Abdullah, Tahirah; Deraman, Siti Nurul Shuhada; Zainuddin, Siti Afiqah; Nawi, Nor Maizana Mat (New Ideas Concerning Science and Technology Vol. 6, 2021)
Presently, the Internet plays a vital role in the life of society. It has also changed the way people travel by providing cheaper, easier and more efficient prices. Recognizing the significant impact of travel applications on the tourism sector, researchers have focused on studies that determine the intention of tourists to use tourism applications. In addition, among the consumer behavior models used to study the tourism sector, is the Unified Acceptance and Use of Technology (UTAUT) model which is a common and new model today. Therefore, the existing study is expected to evaluate the intention of locals to use mobile travel applications based on the UTAUT model. Self-administered questionnaires were distributed to 390 millennials in Malaysia of which IBM SPSS 24 version was selected for data analysis. Studies show that the UTAUT variable is related to behavioral intentions. This study contributes to a new perspective on the use and choice of mobile applications, especially in the context of tourism. It also offers practical application implications for mobile app developers for mobile app feature design, most likely for travelers.